2011
DOI: 10.1097/jcn.0b013e3182076a81
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serotonin in Depression and Clotting in the Coronary Artery Disease Population

Abstract: This review of the literature suggests that elevated platelet serotonin levels may be associated with depression and the occurrence of major adverse coronary events. Future research should investigate if platelet serotonin levels contribute at least in part to the acute coronary events seen in patients with CAD who have elevated levels of platelet serotonin when depressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…In the recent years, the elevated comorbidity rates between cardiovascular disease and depression have occasioned several investigations on the link between them. [ 17 18 ] Our previous studies[ 19 20 ] showed that 5-HT-enhanced platelet activation emerged from this work as a leading candidate explanation of the elevated cardiac risk that attended a diagnosis of major depression.…”
Section: Discussionmentioning
confidence: 91%
“…In the recent years, the elevated comorbidity rates between cardiovascular disease and depression have occasioned several investigations on the link between them. [ 17 18 ] Our previous studies[ 19 20 ] showed that 5-HT-enhanced platelet activation emerged from this work as a leading candidate explanation of the elevated cardiac risk that attended a diagnosis of major depression.…”
Section: Discussionmentioning
confidence: 91%
“…Alterations in the serotonergic system might also explain the link between MD and CAD (10,27). In addition to a central serotonin deficit (28), alterations in peripheral serotonin levels have been suggested: most of peripheral serotonin (5-hydroxy-tryptamine; 5-HT) is stored in platelets and released during platelet activation (29).…”
Section: Introductionmentioning
confidence: 99%
“…The data for individual SIPPS suggest that, for example, sertraline in vitro causes the inhibition of thrombocyte aggregation, depending on its dose [52]. After six weeks of therapy with paroxetine, a normalization of thrombocyte activity can be observed in depressive patients, both in those with and those without the coronary heart disease [53]. Similarly.…”
Section: Discussionmentioning
confidence: 92%